Major phenylpropanoid‐derived metabolites in the human gut can arise from microbial fermentation of protein. Issue 3 (24th January 2013) - Russell, Wendy R.; Duncan, Sylvia H.; Scobbie, Lorraine; Duncan, Gary; Cantlay, Louise; Calder, A. Graham; Anderson, Susan E.; Flint, Harry J.
<x xml:space="preserve">Abstract</x> Scope Plant secondary metabolites, such as phenolic acids are commonly associated with benefits for human health. Two of the most abundant phenylpropanoid‐derived compounds detected in human faecal samples are phenylacetic acid (PAA) and 4‐hydroxylphenylacetic acid (4‐hydroxyPAA). Although they have the potential to be derived from diets rich in plant‐based foods, evidence suggests that these compounds can be derived from the microbial fermentation of aromatic amino acids (AAAs) in the colon. Methods and results To identify the bacteria responsible, 26 strains representing 25 of the dominant human colonic species were screened for phenyl metabolite formation. Seven strains produced significant amounts of both PAA and 4‐hydroxyPAA. These included five out of seven Bacteroidetes (Bacteroides thetaiotaomicron, Bacteroides eggerthii, Bacteroides ovatus, Bacteroides fragilis, Parabacteroides distasonis), and two out of 17 Firmicutes (Eubacterium hallii and Clostridium bartlettii). These species also produced indole‐3‐acetic acid (IAA), the corresponding tryptophan metabolite, but C. bartlettii showed 100 times higher IAA production than the other six strains. Four strains were further tested and PAA formation was substantially increased by phenylalanine, 4‐hydroxyPAA by tyrosine and IAA by tryptophan. Conclusion This study demonstrates that certain microbial species have the ability to ferment all three AAAs and that protein fermentation is the likely source of major phenylpropanoid‐derived metabolites in the colon.